Spontaneous retrobulbar haemorrhage secondary to orbital varices of inferior ophthalmic vein-a case report - Haizul, IM; Umi Kalthum, MN; Mae-Lynn, CB; Faridah, HA (Department of Surgery, UKM Medical Centre, 2012)
A 50-year-old Chinese man presented with sudden onset of painful right eye, diplopia, and redness associated with headache and deteriorating vision. Examination revealed obvious proptosis with elevated intraocular pressure. Computed tomography (CT) scan showed presence of retrobulbar haemmorhage. Emergency lateral canthotomy and cantholysis was performed followed by medical orbital decompression, resulting in improvements in visual acuity, and other ocular symptoms. The diagnosis of thrombosed orbital varices involving inferior ophthalmic vein was confirmed on radiological- angiographic study. To date, he is symptoms-free with good visual acuity. Immediate surgical decompression with lateral cantholysis for retrobulbar haemorrhage was effective in the treatment of retrobulbar haemorrhage.